2021
DOI: 10.15835/nbha49112242
|View full text |Cite
|
Sign up to set email alerts
|

Characterization the coding and non-coding RNA components in the transcriptome of invasion weed Alternanthera philoxeroides

Abstract: Alternanthera philoxeroides is a notorious invasive weed worldwide, but it still lacks a genome information currently. In this study, we collected 4 groups of A. philoxeroides Illumina RNA-seq data (62.5 Gb) and performed a comprehensive de novo assembling. Totally, 421,372 unigenes were obtained with a total length of 230,842,460 bp, with 43,430 (10.31%) unigenes longer than 1000 bp. Then 119,222 (28.3%) unigenes were functional annotated and 235,885 (56.0%) were grouped into reliable lncRNAs reservoir. Besid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The miRNAs are key post-transcriptional regulators [ 18 ]. They are involved in a broad range of plant growth, development, and stress response processes through cleavage and/or inhibition of translation of functional gene transcripts [ 19 ]. In this study, the post-transcriptional regulatory relationships of miRNAs targeting CsDUF966 transcripts were explored.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs are key post-transcriptional regulators [ 18 ]. They are involved in a broad range of plant growth, development, and stress response processes through cleavage and/or inhibition of translation of functional gene transcripts [ 19 ]. In this study, the post-transcriptional regulatory relationships of miRNAs targeting CsDUF966 transcripts were explored.…”
Section: Discussionmentioning
confidence: 99%
“…Three days later, leaf fluorescence was visualized through confocal microscopy (TCS SP8) with 488 nm exciting light wavelength. Gene Ontology database was used to perform functional annotation of TaLIM genes (Zhu, Jiang et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The expression of lincRNAs was divided into four classes (Fig. 3A): (1) low (FPKM ≤ 1); (2) moderate (1 < FPKM ≤ 10); (3) high (10 < FPKM ≤ 100); and (4) very high (100 < FPKM). In each treatment, the majority of lincRNAs belong to the low (41%) and moderate (48%) classes based on lin-cRNA expression; however, some lincRNAs belonged to the high or very high classes, indicating that the lin-cRNAs exhibit a biological purpose, rather than simply representing transcriptional 'noise' (Fig.…”
Section: Expression Pattern Profiling Of Lincrnasmentioning
confidence: 99%
“…In recent years, a growing body of studies has demonstrated that eukaryotic genomes contain many regions that transcribe functional noncoding RNAs (ncRNAs), which are typically grouped into housekeeping and regulatory ncRNAs [1]. Among the regulatory ncR-NAs, long ncRNAs (lncRNAs) have been suggested to be the critical player during eukaryotic gene regulation [2].…”
Section: Introductionmentioning
confidence: 99%